2022
DOI: 10.1098/rsos.220779
|View full text |Cite
|
Sign up to set email alerts
|

Using web-sourced photographs to examine temporal patterns in sex-specific diet of a highly sexually dimorphic raptor

Abstract: Traditional methods to study raptor diet are usually limited temporally, e.g. prey remains at nesting sites, and are unsuitable to examine dietary changes throughout the year. Using web-sourced photography, we explore temporal patterns in prey size and key prey species between sexes of the sexually dimorphic Eurasian sparrowhawk ( Accipiter nisus ) throughout the United Kingdom. We examined 666 photographs of sparrowhawk on prey and identified the prey species involved, together with sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
5
1
Order By: Relevance
“…furcata ) diets found a positive relationship in the proportion of mammal prey in colder environments [ 25 ]. Unlike previous studies which studied the diets of Eurasian Sparrowhawk and Martial Eagles [ 27 , 29 ], we did not find any age effects in the diet of caracaras which may be explained by their generalist nature and tendency to feed on carrion [ 47 , 67 ]. Eurasian Sparrowhawk are avian specialists [ 27 , 28 ] and age-related differences in diet may be more pronounced.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…furcata ) diets found a positive relationship in the proportion of mammal prey in colder environments [ 25 ]. Unlike previous studies which studied the diets of Eurasian Sparrowhawk and Martial Eagles [ 27 , 29 ], we did not find any age effects in the diet of caracaras which may be explained by their generalist nature and tendency to feed on carrion [ 47 , 67 ]. Eurasian Sparrowhawk are avian specialists [ 27 , 28 ] and age-related differences in diet may be more pronounced.…”
Section: Discussioncontrasting
confidence: 99%
“…Our approach, like most methods to study raptor diets [ 8 , 71 ], has been shown to be potentially biased towards larger and more identifiable food items, e.g., mammals and birds, which require longer processing times [ 28 , 29 ]. Consequently, this food-size bias may partly explain why we detected low relative proportions of smaller prey groups, such as invertebrates (2.9%), plant material (0.7%) and amphibians (0.6%) within our photographs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of web-sourced photographs has recently been used to explore the diets of birds (Naude et al 2019;Panter and Amar 2021). This method may suffer from bias, such as being photos more likely to be taken along roadsides, in open habitats, or in lower vegetation levels, but it can provide insight into a time-and cost-effective manner (Berryman and Kirwan 2021;Panter and Amar 2022). Our compilation of natural food sources derived from media associated with records from eastern North America (Suppl.…”
Section: Natural Food Sourcesmentioning
confidence: 99%